Was für eine Europäische Verfassung? - Balibar, Étienne (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2005)
The problem of a European Constitution is discussed at a fundamental level. In which way, can we speak about such a Constitution? Thearticle argues against the “postnational souveranism”, legitimating state against citizens. A new kind of citizenship is favoured based on extended social rights. The constitution now proposed contrarily makes the European Central Bank and its neoliberal policy to central and nearly unchangeable institution.